Intracochlear Measurements of Interaural Time and Level Differences Conveyed by Bilateral Bone Conduction Systems. Issue 10 (December 2017) - Farrell, Nyssa F.; Banakis Hartl, Renee M.; Benichoux, Victor; Brown, Andrew D.; Cass, Stephen P.; Tollin, Daniel J.
Abstract : Hypothesis: Intracochlear pressures (PIC ) and stapes velocity (Vstap ) elicited by bilaterally placed bone-anchored hearing devices (BAHD) will be systematically modulated by imposed interaural time (ITD) and level differences (ILD), demonstrating the potential for users of bilateral BAHD to access these binaural cues. Background: BAHD are traditionally implanted unilaterally under the assumption that transcranial cross-talk limits interaural differences. Recent studies have demonstrated improvements in binaural and spatial performance with bilateral BAHD; however, objective measures of binaural cues from bilateral BAHDs are lacking. Methods: Bone-conduction transducers were coupled to both mastoids of cadaveric specimens via implanted titanium abutments. PIC and Vstap were measured using intracochlear pressure probes and laser Doppler vibrometry, respectively, during stimulation with pure-tone stimuli of varied frequency (250–4000 Hz) under ipsilateral, contralateral, and bilateral ITD (−1 to 1 ms) and ILD (−20 to 20 dB) conditions. Results: Bilateral stimulation produced constructive and destructive interference patterns that varied dramatically with ITD and stimulus frequency. Variation of ITD led to large variation of PIC and Vstap, with opposing effects in ipsilateral and contralateral ears expected to lead to "ITD to ILD conversion." Variation of ILD produced more straightforward (monotonic) variations of PIC and Vstap, with ipsilateral-favoring ILD producing higher PIC and Vstap than contralateral-favoring. Conclusion: Variation of ITDs and ILDs conveyed by BAHDs systematically modulated cochlear inputs. While transcranial cross-talk leads to complex interactions that depend on cue type and stimulus frequency, binaural disparities potentiate binaural benefit, providing a basis for improved sound localization and speech-in-noise perception.